A Systematic Review of Misuse of Antibiotics in Jordan - al-magableh, Mohammad; Eldos, Batool; Aldughmi, Saja; Bani Hamad, Leen; Abdel Karim, Rahaf; Damseh, Roya; Khlouf, Malak (Jordan Medical Journal, 2024)
Background: Antibiotic misuse has become a major global public health issue and this weapon against bacteria is becoming increasingly threatened by the misuse of antibiotics. In Jordan specifically, the availability of antibiotics over the counter, the ease of purchasing antibiotics without prescription, and their misuse could lead to a major health problem. Objectives: This systematic review aims to explore the published literature on antibiotic misuse in Jordan, and to explore the factors contributing to this issue and its effects and propose strategies for reducing antibiotic misuse in Jordan. Methods: Published articles on antibiotic misuse in Jordan from January 2013 to January 2023 were searched via several databases including PubMed, Insight Medical Publishing, ResearchGate, and Semantic Scholar. We included 28 articles discussing the prevalence of antibiotic misuse, knowledge, awareness, and factors contributing to the issue, its impact, and mitigating intervention strategies . Results: The literature indicated a high prevalence of antibiotic misuse among the Jordanian population, especially among children with upper respiratory tract infections. There are numerous reasons for the high prevalence, and several contributing factors were reported, including, but not limited to, cultural factors, financial circumstances, and the level of education. Conclusion: This review highlights antibiotic misuse as a major health problem at the community level and in the Jordanian healthcare system. effective strategies are needed to address this major health challenge.